Preparation method and application of degradable and fluorescent self-repairing polyurethane film
The carbon quantum dots are encapsulated in polylactic acid-based polyurethane through Schiff base reaction, which solves the problems of stability and optical performance of carbon quantum dots in polyurethane, and gives the polyurethane self-healing and degradable functions, achieving efficient material performance improvement.
Patent Information
- Application Number
- CN202411875695.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The prior art is difficult to simultaneously improve the stability of carbon quantum dots, maintain their optical properties, and impart self-healing and degradable functions to polyurethanes.
The carbon quantum dots are encapsulated in polylactic acid-based polyurethane through Schiff base reaction, and the stable binding of the carbon quantum dots and the polyurethane solution is achieved, enhancing the interface binding force and inhibiting agglomeration.
It significantly improves the stability and optical properties of carbon quantum dots, while imparting the self-healing ability and good biodegradability of polyurethane, and is suitable for high-performance smart materials and environmentally friendly materials.
Smart Images

Figure CN119751935A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a preparation method and application of a degradable, fluorescent self-repairing polyurethane film. Background Art
[0002] With the increasing demand for environmental protection and sustainable development, smart materials, especially polymer materials with degradable, fluorescent and self-healing functions, have become a hot topic of research. Carbon quantum dots have been widely used in many fields such as biosensing, optoelectronic devices and environmental monitoring due to their excellent optical properties, biocompatibility and environmental friendliness. However, carbon quantum dots face many challenges in practical applications, especially their poor stability in solid matrices and easy aggregation, which leads to a decrease in their optical properties. Therefore, how to improve the stability of carbon quantum dots while maintaining their excellent optical properties has become a major problem in current technology.
[0003] Polyurethane materials are widely used in the development of smart materials due to their excellent mechanical properties, wear resistance and thermal stability. However, traditional polyurethane is prone to aging, hardening and other problems during long-term use, and cannot self-repair, which limits its application in high-performance smart materials. In order to overcome this shortcoming, researchers have gradually explored the introduction of self-repair mechanisms into polyurethane, so that it can restore its original performance through certain repair mechanisms after damage. In addition, polyurethane materials based on polylactic acid have also become a research focus in recent years due to their good biodegradability and environmental friendliness.
[0004] In the prior art, carbon quantum dots are introduced into polyurethane solution, such as patent CN118206785A, which introduces carbon quantum dots into polyurethane solution by physical blending technology, to prepare carbon quantum dots / aqueous polyurethane composite film, but the following problems still exist: 1) the interfacial bonding between carbon quantum dots and polyurethane matrix is weak; 2) carbon quantum dots are prone to agglomeration in polyurethane matrix; 3) physical blending method cannot effectively improve the stability of carbon quantum dots, which may fall off or migrate during use; 4) the optical properties and mechanical properties of the material are significantly affected by the uneven distribution of carbon quantum dots. Therefore, current research still lacks effective technology that can simultaneously improve the stability of carbon quantum dots, maintain their optical properties, and give polyurethane self-healing and degradable functions. Summary of the invention
[0005] [Technical issues]
[0006] The present invention aims to provide a method for simultaneously improving the stability of carbon quantum dots, maintaining their optical properties, and imparting self-repairing function and degradability to polyurethane.
[0007] [Technical solution]
[0008] In order to solve the above problems, the present invention provides a method for preparing a degradable, fluorescent self-repairing polyurethane film, in which carbon quantum dots are encapsulated in polylactic acid-based polyurethane through a Schiff base reaction, thereby achieving a stable combination of carbon quantum dots and polyurethane solution, having better chemical stability, dispersibility and optical properties, while giving the polyurethane material self-repairing ability and maintaining good biodegradability.
[0009] The present invention provides a method for preparing a degradable, fluorescent self-repairing polyurethane film, which specifically comprises the following steps:
[0010] (1) dissolving o-phenylenediamine and tryptophan in a solvent, adding an acid solution and deionized water to dissolve to obtain a mixed solution, transferring the mixed solution to a Teflon-lined autoclave for reaction, cooling, filtering, dialysis, and freeze-drying after the reaction to obtain carbon quantum dots;
[0011] (2) using isocyanate, polyol and dispersing solvent as raw materials, adding an organic tin catalyst, reacting to obtain a polyurethane oligomer, and adding a chain extender to react to obtain a polyurethane solution;
[0012] (3) Add carbon quantum dots to the polyurethane solution, stir it, and then cast the solution onto a polytetrafluoroethylene substrate for self-leveling. Finally, dry it to obtain a degradable, fluorescent, self-healing polyurethane film.
[0013] In one embodiment of the present invention, in step (1), the solvent is one of anhydrous ethanol, acetone, N,N-dimethylformamide, and dichloromethane, preferably anhydrous ethanol.
[0014] In one embodiment of the present invention, in step (1), the acid solution is one of 12-18 mol / L hydrochloric acid aqueous solution, sulfuric acid aqueous solution, phosphoric acid aqueous solution, and acetic acid aqueous solution, preferably hydrochloric acid aqueous solution.
[0015] In one embodiment of the present invention, in step (1), the mass ratio of o-phenylenediamine to tryptophan is 0.14-0.56:0.528.
[0016] In one embodiment of the present invention, in step (1), the reaction temperature is 120-220° C., and the reaction time is 4-10 h.
[0017] In one embodiment of the present invention, in step (1), the volume ratio of the solvent, the acid solution, and the deionized water is 10-30:1-5:2-10.
[0018] In one embodiment of the present invention, in step (2), after adding the organotin catalyst, the reaction temperature is 30 to 60° C. and the reaction time is 1 to 5 hours.
[0019] In one embodiment of the present invention, in step (2), the isocyanate is one of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2-diphenylmethane diisocyanate, 4,4-diphenylmethane diisocyanate, isophorone diisocyanate, 1,3-butadiene-1,4-diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, 1,6,11-undecane triisocyanate, preferably 1,6-hexamethylene diisocyanate.
[0020] In one embodiment of the present invention, in step (2), the polyol is polylactic acid polyol.
[0021] In one embodiment of the present invention, in step (2), the dispersing solvent is one of acetone, cyclohexanone, 1,4-dioxane, N,N-dimethylformamide, and methyl tert-butyl ether, preferably N,N-dimethylformamide.
[0022] In one embodiment of the present invention, in step (2), the organotin catalyst is one of diisobutyltin dilaurate, stannous octoate, dibutyltin didodecylsulfide, and dibutyltin diacetate, preferably diisobutyltin dilaurate.
[0023] In one embodiment of the present invention, in step (2), the added amounts of isocyanate, polyol and dispersing solvent are 0.01-0.05 mol:0.01 mol:5-30 mL, and the volume ratio of the organotin catalyst to the dispersing solvent is 0.05-0.25 mL:5-30 mL.
[0024] In one embodiment of the present invention, in step (2), a chain extender is added, the temperature is adjusted to 60-100° C., and the reaction is carried out for 1-3 hours. After the reaction is completed, a polyurethane solution is obtained.
[0025] In one embodiment of the present invention, in step (2), the chain extender is 2-hydroxyethyl disulfide.
[0026] In one embodiment of the present invention, in step (2), the molar ratio of the chain extender to the polyol is 0.2 to 0.8:1.
[0027] In one embodiment of the present invention, in step (3), the amount of carbon quantum dots added is 0.01 to 0.25% of the mass of the polyurethane solution.
[0028] The present invention provides a degradable, fluorescent self-repairing polyurethane film prepared by the method described above.
[0029] The present invention also provides application of the above-mentioned degradable and fluorescent self-repairing polyurethane film on fabrics.
[0030] [Beneficial Effects]
[0031] (1) The present invention significantly improves the stability of carbon quantum dots: The present invention effectively encapsulates carbon quantum dots in a polyurethane matrix through a Schiff base reaction. The present invention can effectively inhibit the aggregation of carbon quantum dots in a solid matrix, significantly improve its stability and durability in long-term use, and ensure that the carbon quantum dots can still maintain good optical properties under different environmental conditions.
[0032] (2) The present invention retains excellent fluorescence properties: By using polylactic acid-based polyurethane materials, the present invention can improve the stability of carbon quantum dots while maintaining their excellent fluorescence properties, ensuring the application advantages of the material in optoelectronics, sensing and other fields, and meeting the dual requirements of high-performance fluorescent materials for stability and brightness.
[0033] (3) The present invention improves the self-repairing ability of the material: By introducing a self-repairing mechanism, the present invention enables the polyurethane material to restore its original physical properties through internal chemical reactions after being damaged by external forces, thereby greatly extending the service life of the material. The material is particularly suitable for the field of smart materials and environmentally friendly materials that have high requirements for long-term use and durability.
[0034] (4) The present invention has good biodegradability and environmental protection characteristics: Since polylactic acid is a degradable material, the prepared fluorescent self-healing polyurethane not only has good biodegradability, but also can be naturally decomposed in the environment, which meets the demand of modern society for green and environmentally friendly materials, reduces resource waste and environmental pollution, and promotes the development of sustainable materials.
[0035] (5) The present invention provides a simple, economical and environmentally friendly preparation process: The present invention provides a simple, low-cost and environmentally friendly preparation method, which can efficiently synthesize the required materials under mild conditions, and the raw materials used are non-toxic and harmless, meeting the requirements of green chemistry. The preparation process can be applied on a large scale in industrial production and has significant economic benefits and social value.
[0036] (6) Application of the present invention in flaw detection: The polyurethane material of the present invention has significant advantages in flaw detection applications, which is mainly reflected in the use of changes in the fluorescence brightness of the polyurethane material surface. When a flaw appears on the surface of the polyurethane material, the refraction and reflection characteristics of light at the flaw change, resulting in a significant increase in the fluorescence brightness of the area. Through this phenomenon, the presence of the flaw can be detected quickly and accurately, which has strong practicality and is particularly suitable for the field of high-performance textiles, and can improve product quality control and safety of use. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is a transmission electron microscope image of the carbon dots of Example 1 of the present invention;
[0038] Figure 2 is an infrared spectrum of carbon dots and polyurethane in Example 1 of the present invention;
[0039] Figure 3 is the excitation and emission spectra of the carbon dots in Example 1 of the present invention;
[0040] Figure 4 These are scanning electron microscope images of the polyurethane film of Example 1 of the present invention before (a) and after (b) degradation;
[0041] Figure 5 This is a diagram of the self-repairing process of the polyurethane film in Example 1 of the present invention;
[0042] Figure 6 1 is a fluorescent photograph of an X-shaped crack on the surface of the film of Example 1 of the present invention (a) and a fluorescent schematic diagram of cracks on the surface of the film (b);
[0043] Figure 7 1 is the emission spectra of the carbon dot solution of Example 1 of the present invention (red line) and the carbon dot solution after being placed for 15 days (black line);
[0044] Figure 8 : are the emission spectra of the polyurethane film of Example 1 of the present invention (purple line) and the polyurethane film after being placed for 15 days (blue line);
[0045] Fig. 9 is a photograph of the fluorescent polyurethane hot-pressed fabric of Example 1 of the present invention under visible light and ultraviolet light;
[0046] Fig.10 It is the synthesis route diagram of the present invention. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described in detail below through specific embodiments. However, it is necessary to point out that the following embodiments are only used to describe the content of the invention and do not constitute a limitation on the protection scope of the present invention.
[0048] The polylactic acid polyol used in the following examples was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., with the name: polylactic acid diol 2000, molecular weight 2000, batch number: 2024-712.
[0049] The test method used in the present invention is:
[0050] (1) Transmission electron microscopy analysis of carbon quantum dots
[0051] The carbon quantum dots were analyzed using an American FEI Talos F200x transmission electron microscope, with the operating voltage set to 200 kV.
[0052] (2) Infrared spectroscopy testing of carbon quantum dots and polyurethane
[0053] Sample spectral data were collected at room temperature using a Thermo Scientific Nicolet is10 FTIR spectrometer equipped with a diamond ATR crystal. The spectral coverage range was from 4000 to 400 cm -1 , with a resolution of 32 scans.
[0054] (3) Fluorescence spectrum test
[0055] The fluorescence spectrum of the carbon quantum dot sample was tested using a Hitachi F-7000 fluorescence spectrophotometer. The instrument was preheated and set to an excitation wavelength of 535 nm, a fluorescence emission spectrum scanning range of 555-750 nm, a slit width of 5 nm, and a scanning speed of 1200 nm / min.
[0056] (4) Testing of tensile and self-healing properties of polyurethane
[0057] The self-healing properties and mechanical properties of polyurethane were evaluated using an electronic universal testing machine. The tensile rate was set to 200 mm / min. According to GB / T 1040.3-2006, the PU samples were cut into dumbbell specimens with a size of 20 mm × 4 mm × 0.5 mm. The average value of each sample was tested 3 times, and the average value was taken as the final result. The self-healing efficiency was calculated using formula (1), where δ0 is the fracture strength of the original sample, δ1 is the fracture strength of the repaired sample, and the self-healing efficiency is represented by η.
[0058]
[0059] (5) Degradation performance test
[0060] The morphology of polyurethane before and after degradation was examined using a Regulus 8100 scanning electron microscope (Tokyo, Japan) at an accelerating voltage of 5.0 kV. Before SEM imaging, the surface of each sample was prepared by sputtering a fine layer of gold.
[0061] (6) Microscope testing of polyurethane
[0062] An optical microscope with magnification of 10×20 was used to observe the scratches and repair status of the polyurethane before and after self-repair, and the self-repair effect was evaluated by comparing the photos before and after repair.
[0063] (7) Fluorescent polyurethane scar detection effect test
[0064] The P(60)6 standard light source light box produced by Shanghai Carlo Kachao Instrument Co., Ltd. was used to test the fluorescence effect of fluorescent polyurethane under standard light source and ultraviolet light source.
[0065] Example 1
[0066] A method for preparing a degradable, fluorescent self-repairing polyurethane film comprises the following steps:
[0067] (1) 0.187 g of o-phenylenediamine and 0.528 g of tryptophan were dissolved in 20 mL of anhydrous ethanol, and then 1 mL of 12 mol / L hydrochloric acid and 4 mL of water were added. The resulting mixture was subjected to ultrasonic treatment to ensure thorough dissolution, and then transferred to a polytetrafluoroethylene-lined autoclave. The reaction was carried out at 180° C. for 6 h. After completion, the autoclave was naturally cooled to room temperature, and then the crude aqueous solution was filtered through a 0.22 μm filter membrane to remove impurities and agglomerated particles. Subsequently, the filtered solution was extensively dialyzed using a 500 Da dialysis bag for 3 days to remove specific by-products and unreacted precursors, and finally a black powder was obtained by freeze drying, i.e., carbon quantum dots were obtained;
[0068] (2) 0.01 mol of polylactic acid polyol and 0.02 mol of 1,6-hexamethylene diisocyanate were transferred to a three-necked round-bottom flask, 20 mL of N,N-dimethylformamide and 0.25 mL of diisobutyltin dilaurate as a catalyst were added, and the reaction was maintained at 40°C for 1 h. Subsequently, 0.005 mol of 2-hydroxyethyl disulfide was added as a chain extender, the temperature was adjusted to 85°C, and the reaction was extended for another 2 h to obtain a polyurethane solution after the reaction;
[0069] (3) 6 g of polyurethane solution was added with 0.0006 g of carbon quantum dots and stirred at room temperature for 3 h. The solution was degassed in a vacuum dryer at ambient temperature for 30 min and then cast onto a polytetrafluoroethylene substrate for self-leveling. The film was then dried in a vacuum oven at 70 °C for 48 h to eliminate residual solvent, thereby preparing a degradable, fluorescent self-healing polyurethane film.
[0070] A biodegradable, fluorescent self-repairing polyurethane hot-pressed fabric: a pre-prepared film and a silk fabric are combined in a hot press, and the set conditions are a temperature of 90° C., a pressure of 8 MPa, and a duration of 10 minutes to obtain a fluorescent self-repairing polyurethane hot-pressed fabric.
[0071] The carbon dots of the present invention show characteristic lattice fringes of 0.208 nm, which is consistent with the (100) plane lattice spacing of graphene ( Figure 1 ).
[0072] Carbon dots at 3396 cm -1 A prominent characteristic peak is shown at 2855 cm-1, which corresponds to -NH2. This indicates that there are amino groups on the surface of carbon dots, which provide important reaction sites for the subsequent Schiff base reaction. -1 and 1744cm -1The characteristic peaks at 1664 cm-1 and 1674 cm-2 in the CDs@PU composites correspond to the vibrations of -CH- and -C=O, indicating the presence of these functional groups, which confirm the formation of the polyurethane structure and also provide sites for potential covalent bonds between polyurethane and carbon dots. -1 A new peak was observed at , which was attributed to the stretching vibration of -C=N-. The appearance of this peak clearly indicated that the Schiff base reaction had successfully occurred, indicating that the carbon dots had been effectively covalently grafted onto the polyurethane matrix ( Figure 2 ).
[0073] Fluorescence spectra showed that after excitation at 535 nm, the optimal emission wavelength of carbon dots was determined to be 600 nm ( Figure 3 Before degradation, the polyurethane film showed a smooth and uniform surface morphology. After 15 days of soil degradation, the surface morphology of all samples changed significantly. The polyurethane showed obvious signs of surface erosion, with microcracks and pits, indicating that the material was biodegradable ( Figure 4 ). Figure 5 The self-healing process of a polyurethane film is illustrated, showing the material in its original, damaged, and repaired states. After the composite material is damaged, the integrity of the material is restored by heating, and the previously visible cracks have almost disappeared after healing. Figure 6 As shown in Figure 3, an X-shaped crack is formed on the surface of the polyurethane film. Under 365nm ultraviolet irradiation, the fluorescence intensity of this area increases significantly. This fluorescence enhancement is directly attributed to the optical phenomena occurring at the fracture. Specifically, Figure 6 As shown in (b), the roughness of the crack surface causes multiple refraction and scattering of ultraviolet light within the crack, and the geometry of the crack causes multiple refraction and reflection of light, thereby enhancing light capture and amplification of the fluorescence signal.
[0074] After 15 days of storage, the fluorescence intensity of the original carbon dot solution decreased by more than 1000 ( Figure 7 ), after the polyurethane film was placed for 15 days, it only dropped by about 300-400 during the same period, which proved the stability of carbon quantum dots.
[0075] Photos of polyurethane hot pressed fabrics under visible light and ultraviolet light are shown in Figure 2. Fig. 9 shown.
[0076] Example 2
[0077] A method for preparing a degradable, fluorescent self-repairing polyurethane film comprises the following steps:
[0078] 0.280 g of o-phenylenediamine and 0.528 g of tryptophan were dissolved in 25 mL of anhydrous ethanol, and then 1.5 mL of 12 mol / L hydrochloric acid solution and 5 mL of deionized water were added. The mixture was ultrasonically treated at 40 ° C for 20 min and then transferred to a polytetrafluoroethylene-lined autoclave. The reaction was carried out at 150 ° C for 8 h. After completion, it was cooled to room temperature, the crude aqueous solution was filtered and dialyzed for 4 days to remove impurities, and finally freeze-dried to obtain a black powder, i.e., carbon quantum dots were obtained;
[0079] 0.01 mol of polylactic acid polyol and 0.015 mol of 1,6-hexamethylene diisocyanate were transferred to a three-necked round-bottom flask, 25 mL of N,N-dimethylformamide and 0.15 mL of diisobutyltin dilaurate catalyst were added, and the mixture was reacted at 60 ° C for 2 h, followed by addition of 0.002 mol of 2-hydroxyethyl disulfide as a chain extender, the temperature was adjusted to 90 ° C, and the reaction was extended for 3 h to obtain a polyurethane solution;
[0080] Take 8 g of polyurethane solution, add 0.0008 g of carbon quantum dots, stir for 4 h, degas the solution in a vacuum dryer at ambient temperature for 30 min, then cast it onto a polytetrafluoroethylene substrate for self-leveling, and then dry it in a vacuum oven at 70 °C for 48 h to eliminate residual solvent, thereby preparing a degradable, fluorescent self-healing polyurethane film.
[0081] A biodegradable, fluorescent self-repairing polyurethane hot-pressed fabric: a pre-prepared film and a silk fabric are combined in a hot press, and the set conditions are a temperature of 90° C., a pressure of 8 MPa, and a duration of 10 minutes to obtain a fluorescent self-repairing polyurethane hot-pressed fabric.
[0082] Example 3
[0083] A method for preparing a degradable, fluorescent self-repairing polyurethane film comprises the following steps:
[0084] 0.140 g of o-phenylenediamine and 0.528 g of tryptophan were dissolved in 30 mL of anhydrous ethanol, 2 mL of 12 mol / L hydrochloric acid and 3 mL of water were added, the mixture was ultrasonicated at 30 ° C for 10 min and then transferred to an autoclave, the reaction was carried out at 200 ° C for 6 h, and after cooling, dialyzed for 3 days and dried to obtain a carbon quantum dot black powder, that is, carbon quantum dots were obtained;
[0085] Take 0.01 mol of polylactic acid polyol and 0.025 mol of 1,6-hexamethylene diisocyanate, add 15 mL of N,N-dimethylformamide, drop 0.05 mL of diisobutyltin dilaurate, react at 50°C for 1 hour, then add 0.006 mol of chain extender 2-hydroxyethyl disulfide, adjust the temperature to 80°C, and react for 2 hours to obtain a polyurethane solution;
[0086] Take 4 g of polyurethane solution, add 0.0005 g of carbon quantum dots, stir for 2 h, degas the solution in a vacuum dryer at ambient temperature for 30 min, then cast it onto a polytetrafluoroethylene substrate for self-leveling, and then dry it in a vacuum oven at 70 °C for 48 h to eliminate residual solvent, thereby preparing a degradable, fluorescent self-healing polyurethane film.
[0087] A biodegradable, fluorescent self-repairing polyurethane hot-pressed fabric: a pre-prepared film and a silk fabric are combined in a hot press, and the set conditions are a temperature of 90° C., a pressure of 8 MPa, and a duration of 10 minutes to obtain a fluorescent self-repairing polyurethane hot-pressed fabric.
[0088] Example 4
[0089] A method for preparing a degradable, fluorescent self-repairing polyurethane film comprises the following steps:
[0090] 0.420 g of o-phenylenediamine and 0.528 g of tryptophan were dissolved in 15 mL of anhydrous ethanol, 3 mL of 12 mol / L hydrochloric acid solution and 6 mL of water were added, the mixture was ultrasonicated for 30 min and then transferred to an autoclave, the reaction was carried out at 170 ° C for 10 h, and after cooling, it was filtered and dialyzed for 5 days, and then dried to obtain carbon quantum dot powder, that is, carbon quantum dots were obtained;
[0091] 0.01 mol of polylactic acid polyol and 0.03 mol of 1,6-hexamethylene diisocyanate were transferred to a three-necked round-bottom flask, 30 mL of N,N-dimethylformamide and 0.1 mL of stannous octoate catalyst were added, and the mixture was reacted at 55°C for 3 h, followed by addition of 0.008 mol of 2-hydroxyethyl disulfide chain extender, and the temperature was adjusted to 95°C for 1 h to obtain a polyurethane solution;
[0092] After 10 g of polyurethane solution and 0.001 g of carbon quantum dots were stirred for 5 h, the solution was degassed in a vacuum dryer at ambient temperature for 30 min and then cast onto a polytetrafluoroethylene substrate for self-leveling and then dried in a vacuum oven at 70 °C for 48 h to eliminate residual solvent, thereby preparing a degradable, fluorescent self-healing polyurethane film.
[0093] A biodegradable, fluorescent self-repairing polyurethane hot-pressed fabric: a pre-prepared film and a silk fabric are combined in a hot press, and the set conditions are a temperature of 90° C., a pressure of 8 MPa, and a duration of 10 minutes to obtain a fluorescent self-repairing polyurethane hot-pressed fabric.
[0094] Example 5
[0095] A method for preparing a degradable, fluorescent self-repairing polyurethane film comprises the following steps:
[0096] 0.187 g of o-phenylenediamine and 0.528 g of tryptophan were dissolved in 25 mL of dichloromethane, 2 mL of 18 mol / L sulfuric acid solution and 6 mL of water were added, the mixture was ultrasonically treated for 20 min and then transferred to an autoclave, the reaction was carried out at 190 ° C for 8 h, cooled, dialyzed for 3 days and then dried to obtain a black powder, i.e., carbon quantum dots;
[0097] Take 0.01 mol of polylactic acid polyol and 0.04 mol of isophorone diisocyanate, add 20 mL of N,N-dimethylformamide, dropwise add 0.25 mL of catalyst diisobutyltin dilaurate, react at 45°C for 2 h, then add 0.004 mol of chain extender 2-hydroxyethyl disulfide, adjust the temperature to 80°C and react for 1.5 h to obtain a polyurethane solution;
[0098] 5 g of polyurethane solution and 0.0006 g of carbon quantum dots were taken and mixed for 3 h. The solution was degassed in a vacuum dryer at ambient temperature for 30 min and then cast onto a polytetrafluoroethylene substrate for self-leveling. It was then dried in a vacuum oven at 70 °C for 48 h to eliminate residual solvent, thereby preparing a degradable, fluorescent self-healing polyurethane film.
[0099] A biodegradable, fluorescent self-repairing polyurethane hot-pressed fabric: a pre-prepared film and a silk fabric are combined in a hot press, and the set conditions are a temperature of 90° C., a pressure of 8 MPa, and a duration of 10 minutes to obtain a fluorescent self-repairing polyurethane hot-pressed fabric.
[0100] Comparative Example 1
[0101] 0.01 mol 2,6-toluene diisocyanate, 0.02 mol polytetrahydrofuran diol, and 10 mL N,N-dimethylformamide were added into a 500 mL four-necked flask at one time, 0.25 mL catalyst diisobutyltin dilaurate was added dropwise, and the reaction was carried out at 60 ° C for 2 h, followed by adding 0.004 mol chain extender 2,2-dihydroxymethylpropionic acid, adjusting the temperature to 90 ° C for 1.5 h to obtain a polyurethane solution. The solution was degassed in a vacuum dryer at ambient temperature for 30 min, and then cast onto a polytetrafluoroethylene substrate for self-leveling, and then dried in a vacuum oven at 70 ° C for 48 h to eliminate residual solvents to obtain a control polyurethane.
[0102] Comparative Example 2
[0103] Weigh 0.1g lignin and 0.1g o-phenylenediamine, dissolve in 20mL ethanol, ultrasonically disperse for 10min, transfer the solution to a tetrafluoroethylene-lined reactor, and seal it well. React in a 200℃ oven for 5h, and cool to room temperature to obtain a crude product. Carbon quantum dots are obtained by centrifuging, dialyzing, and freeze-drying the crude product; the centrifugation is performed at a speed of 10000r / min for 10min; the dialysis is performed using a dialysis bag with a molecular weight cutoff of 1000Da.
[0104] Add 5 mL of 1 mg / mL carbon quantum dot ethanol solution to 10 g of waterborne polyurethane (solid content 30%) and disperse it with ultrasound for 30 min. Let it stand for 24 h and heat it at 130 °C for 2 h. A waterborne polyurethane / carbon quantum dot composite film with a mass fraction of 0.167 wt% was successfully prepared.
[0105] Table 1 Performance test results of polyurethane films obtained in Examples 1 to 5 and Comparative Examples 1 to 2
[0106]
[0107] A degradable, fluorescent self-repairing polyurethane prepared by the present invention exhibits different tensile properties and self-repairing abilities by optimizing various performance parameters. Examples 1 and 2 excel in tensile elongation and self-repairing efficiency, especially Example 2 is outstanding in tensile strength and self-repairing ability, and is suitable for applications with high strength and certain repair requirements. Examples 3 and 5 are slightly inferior in performance, but still have good tensile properties and self-repairing abilities, and are suitable for medium strength applications. Example 4 is relatively inferior in various properties and is suitable for occasions with low strength requirements. In general, the polyurethane material prepared by the present invention has good adjustability and can meet the performance requirements of different applications.
[0108] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a degradable, fluorescent self-repairing polyurethane film, characterized in that: The steps include: (1) dissolving o-phenylenediamine and tryptophan in a solvent, adding an acid solution and deionized water to dissolve to obtain a mixed solution, transferring the mixed solution to a Teflon-lined autoclave for reaction, cooling, filtering, dialysis, and freeze-drying after the reaction to obtain carbon quantum dots; (2) using isocyanate, polyol and dispersing solvent as raw materials, adding an organic tin catalyst, reacting to obtain a polyurethane oligomer, and adding a chain extender to react to obtain a polyurethane solution; (3) Add carbon quantum dots to the polyurethane solution, stir it, and then cast the solution onto a polytetrafluoroethylene substrate for self-leveling. Finally, dry it to obtain a degradable, fluorescent, self-healing polyurethane film.
2. The method for preparing a degradable, fluorescent self-repairing polyurethane film according to claim 1, characterized in that: In step (1), the solvent is one of anhydrous ethanol, acetone, N,N-dimethylformamide, and dichloromethane; the acid solution is one of a 12-18 mol / L hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, a phosphoric acid aqueous solution, and an acetic acid aqueous solution.
3. The method for preparing a degradable, fluorescent self-repairing polyurethane film according to claim 1, characterized in that: In step (1), the mass ratio of o-phenylenediamine to tryptophan is 0.14-0.56:0.528; the volume ratio of the solvent, the acid solution, and the deionized water is 10-30:1-5:2-10.
4. The method for preparing a degradable, fluorescent self-repairing polyurethane film according to claim 1, characterized in that: In step (1), the reaction temperature is 120-220° C. and the reaction time is 4-10 h.
5. The method for preparing a degradable, fluorescent self-repairing polyurethane film according to claim 1, characterized in that: In step (2), the isocyanate is one of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2-diphenylmethane diisocyanate, 4,4-diphenylmethane diisocyanate, isophorone diisocyanate, 1,3-butadiene-1,4-diisocyanate, 2,4,4-trimethyl 1,6-hexane diisocyanate, and 1,6,11-undecane triisocyanate; the polyol is polylactic acid polyol; the dispersing solvent is one of acetone, cyclohexanone, 1,4-dioxane, N,N-dimethylformamide, and methyl tert-butyl ether; and the organotin catalyst is one of diisobutyltin dilaurate, stannous octoate, dibutyltin didodecylsulfide, and dibutyltin diacetate.
6. The method for preparing a degradable, fluorescent self-repairing polyurethane film according to claim 1, characterized in that: In step (2), the added amounts of isocyanate, polyol and dispersing solvent are 0.01-0.05 mol:0.01 mol:5-30 mL; and the volume ratio of the organotin catalyst to the dispersing solvent is 0.05-0.25 mL:5-30 mL.
7. The method for preparing a degradable, fluorescent self-repairing polyurethane film according to claim 1, characterized in that: In step (2), an organic tin catalyst is added to carry out a reaction at a reaction temperature of 30 to 60° C. and a reaction time of 1 to 5 hours; a chain extender is added, the temperature is adjusted to 60 to 100° C., and the reaction is carried out for 1 to 3 hours. After the reaction is completed, a polyurethane solution is obtained; the chain extender is 2-hydroxyethyl disulfide; and the molar ratio of the chain extender to the polyol is 0.2 to 0.8:
1.
8. The method for preparing a degradable, fluorescent self-repairing polyurethane film according to claim 1, characterized in that: In step (3), the carbon quantum is 0.01 to 0.25% of the mass of the polyurethane solution.
9. A degradable, fluorescent self-repairing polyurethane film prepared by the method of any one of claims 1 to 8.
10. Use of the degradable, fluorescent self-repairing polyurethane film according to claim 9 on fabrics.
Citation Information
Patent Citations
Carbon quantum dot modified waterborne polyurethane nanocomposite and preparation method thereof
CN108822527A
Disulfide bond-based bio-based degradable cross-linked self-repairing polyurethane and preparation method thereof
CN112126036A
Preparation method of aminated carbon quantum dot degradable fluorescent film
CN115260723A
Preparation method and application of carbon quantum dot modified hydrogel
CN117582538A
Self-repairable, repeatedly-processed and degradable polyurethane material based on multi-bond action and preparation method of self-repairable, repeatedly-processed and degradable polyurethane material
CN118930793A
Cited By
A heat-resistant self-repairing polyurethane elastic system and preparation method thereof
CN120289748B
Composite biofilm carrier as well as preparation method and application thereof
CN121449212A